A World Ruled by Number : William Stanley Jevons and the Rise of Mathematical Economics. - Schabas, Margaret (Princeton legacy library., 2014)
If any single characteristic differentiates current, neoclassical economics from the classical economics of Adam Smith and David Ricardo, it is the use of mathematics. Pointing to the critical role of William Stanley Jevons (1835-1882), Margaret Schabas demonstrates that the advent of mathematical economics in late Victorian England resulted more from new currents in logic and the philosophy of science than from problems specific to the classical theory of value and distribution. Jevons's Principles of Science (1874) was the first book to take issue with John Stuart Mill's faith in in.